Will your child take care of you in your old age? Unequal caregiving received by older parents from adult children in Sweden. - von Saenger, Isabelle; Dahlberg, Lena; Augustsson, Erika; Fritzell, Johan; Lennartsson, Carin (European Journal of Ageing, 2023)
Intergenerational family care provided to older parents by adult children is growing and differs based on gender and socioeconomic status. Few studies consider these elements in relation to both the parent and their adult child, and little is known about the number of care tasks received even though those providing intensive levels of care are at risk of experiencing adverse consequences in their lives. This study uses data from the nationally representative 2011 Swedish Panel Study of Living Conditions of the Oldest Old (SWEOLD) and includes child-specific information from parents aged 76 years and above. Analyses used ordinal logistic regression and are presented as average marginal effects and predictive margins. Results show that parents in need of care report that one-third of all adult children in the sample provide care to three out of five of them. The care is most often non-intensive, yet nearly one in ten of all children provide more intensive care of two or more tasks. When adjusting for dyad characteristics as well as geographic proximity, results show adult–child gender differences where parents receive more care from manual-working-class daughters than manual-working-class sons. Overall, manual-working-class daughters are most commonly reported as carers among adult children, and they are particularly overrepresented in providing intensive care. We conclude that gender and socioeconomic inequalities exist among care receivers’ adult children, even in a strong welfare state such as Sweden. Knowledge about levels and patterns of intergenerational care have important implications for how to reduce unequal caregiving.